2019
DOI: 10.1007/s00467-018-4191-0
|View full text |Cite
|
Sign up to set email alerts
|

Malaria and acute kidney injury

Abstract: Malaria is a parasitic infection transmitted by mosquitos, resulting in significant morbidity and mortality. It affects 212 million worldwide, causing death in up to 303,000 children annually. In the USA, up to 1700 people are affected yearly. Although the prevalence in developed countries is less than in developing countries, travelers from low transmission areas, and those from endemic areas who later return, are very susceptible to malaria and its complications. Severe malaria can cause significant multiorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 48 publications
(70 reference statements)
1
29
0
Order By: Relevance
“…Multiple studies have identified malaria as one of the most frequent etiologies of pediatric AKI cases in developing countries (58). Importantly, both adult and pediatric studies have shown that when AKI occurs in the context of malaria, there is an increase in patient mortality (59,60). One of the key questions that remains to be answered is whether AKI plays a causal role in SM deaths, or if it is a consequence of pathological processes which lead to death through their effects on other organs.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have identified malaria as one of the most frequent etiologies of pediatric AKI cases in developing countries (58). Importantly, both adult and pediatric studies have shown that when AKI occurs in the context of malaria, there is an increase in patient mortality (59,60). One of the key questions that remains to be answered is whether AKI plays a causal role in SM deaths, or if it is a consequence of pathological processes which lead to death through their effects on other organs.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced serum levels of AST, ALT, total bilirubin, and indirect bilirubin observed in response to treatment suggest that R. japonicus could protect P. berghei -infected animals against liver damage, thus improving their clinical status. Moreover, malaria infection also results in renal damage due to alteration of renal blood circulation caused by conformational changes of parasitized erythrocytes, increased blood viscosity, and cytoadherence of infected erythrocytes [ 23 ]. The observed decreases in serum levels of urea and creatinine suggest that reductions in parasitemia in response to administration of the RJE may also prevent erythrocyte adherence, high blood viscosity, dysfunctional renal blood circulation, and subsequent renal injury.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate of malaria-associated AKI reached up to 51%, and worst prognosis was associated with delayed referral, severe jaundice, oliguria, and multi-organ involvement. 12 The pathogenesis of AKI is believed to be caused by infected red blood cell (RBC) sequestration in the renal vasculature leading to hypoperfusion and tissue hypoxia, combined with immune complex deposition in renal tubules. Malaria-induced AKI manifests pathologically as acute tubular necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of AKI is suspected when urine output falls to <400 mL/24 hours and should be confirmed when serum creatinine level reaches 3 mg/dL or higher. 12 Jaundice is another common manifestation of severe malaria. Jaundice associated with malaria is often biphasic in nature, with elevation of both conjugated and nonconjugated bilirubin contributed by cholestasis and hemolysis of RBC, respectively.…”
Section: Discussionmentioning
confidence: 99%